Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1593/neo.04310
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Stem Cells from Human Neuroblastoma Cell Lines and in Tumors

Abstract: Cellular heterogeneity is a hallmark of human neuroblastoma tumors and cell lines. Within a single neuroblastoma are cells from distinct neural crest lineages whose relative abundance is significant for prognosis. We postulate that a self-renewing multipotent tumor stem cell, which gives rise to diverse cell lineages, is the malignant progenitor of this cancer. To test this hypothesis, we have established 22 cloned, phenotypically homogeneous populations of the three major cell types from 17 neuroblastoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
253
0
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(281 citation statements)
references
References 16 publications
13
253
0
10
Order By: Relevance
“…Given that long-term in vitro culture could result in growth of selected tumor cell subsets, it is important to validate these findings with primary or short-passage human neuroblastoma cells (47). It is well documented that MDSCs and TAMs are associated with poor clinical outcome in patients with solid tumors (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Given that long-term in vitro culture could result in growth of selected tumor cell subsets, it is important to validate these findings with primary or short-passage human neuroblastoma cells (47). It is well documented that MDSCs and TAMs are associated with poor clinical outcome in patients with solid tumors (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…These subtypes have distinct biochemical, morphologic and tumorigenic properties, mimicking the clinical and pathologic heterogeneity of clinical NB. 18 …”
Section: Neuroblastoma Tumors and Cell Linesmentioning
confidence: 99%
“…Stem cells derived from I type have more ability to differentiate into different cell types than other types, having a high colony-forming capacity and high growth potential in immunodeficient mice. It has been proved that malignant stem cell phenotype (CD133 and c-kit expression), but not MYCN amplification status or its expression, defines the tumorigenic potential of the various NBL cell lines [52]. Those results were also proved by examination of 40 tumor samples which showed that percentage of CD133+ cells was higher in neuroblastoma than in ganglioneuroblastoma, correlated with clinical stage, and was higher in tumors with unfavorable than favorable histology.…”
mentioning
confidence: 96%